A community-based study to evaluate the prevalence and risk factors for osteoporosis among menopausal and pre-menopausal women - Thangappah, Radha B. P.; Madhavan, T. M. Vaishnavi; Dharmalingam, Poovizhi; Palanisamy, Anitha; Senthilkumar, Mohana Priya A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: To determine the prevalence of osteoporosis among pre and post menopausal women using quantitative ultrasound of calcaneal bone and to identify the risk factors associated with osteoporosis. Methods: This prospective community based epidemiological study was conducted during 2019 in a suburban area attached to Sri Muthu Kumaran Medical College Hospital and Research Institute, Chennai. 305 subjects met the inclusion and exclusion criteria. Using a structured questionnaire, demographic details, obstetric, gynaecological and medical history were collected. Quantitative ultrasound of the calcaneal bone was used to calculate the bone mineral density. Using statistical methods, risk factors for osteoporosis were analysed. Results: The mean age of the participants was 52.67±9.41 years, 62.2% were post menopausal and 37.38% were premenopausal. The BMD ‘T’ score was normal in 29.8%, osteopenia was diagnosed in 38.4% and osteoporosis in 31.8% of participants. 14% of premenopausal women and 42.4% of postmenopausal women were osteoporotic. Age, menopausal status, duration of menopause, and previous history of fractures emerged as significant risk factors for osteoporosis. Conclusions: The prevalence of osteoporosis is high among both pre-menopausal and menopausal women, but the awareness is limited. This study highlights the need for screening all women after the age of 40 years which is feasible using portable and easily available technology such as quantitative ultrasound of peripheral bones.